THE REGULATION OF PIRACY AND ARMED ROBBERY AT SEA IN INTERNATIONAL LAW - Gerald Aldytia Bunga (Jurnal Hukum dan Peradilan, 2020)
This paper examines the regulation of piracy and armed robbery at sea in international law applicable globally and applicable only in a certain region. This research will review the elements of piracy and armed robbery at sea then made a distinction between both crimes. It will be found that there are problems that still not legally regulated in existing international regulation concerning piracy and armed robbery at sea or it has been regulated but still cause a problem in the prosecution of both crimes. It is a normative research which concludes that the regulation of armed robbery at sea is found only in regional international legal rules, unlike the regulation of piracy that exists in international rules that applied globally. The existing regulations leave problems concerning areas where a crime such as piracy-like act will be difficult to categorize as piracy or armed robbery at sea.